Figuras fulgurantes: a geometrização do espaço Llansol - Vitagliano, Karina Marize [UNESP]; Piteri, Sônia Helena de Oliveira Raymundo [UNESP] (My University, 2010)
Os pregos na erva (1962), the first book by Maria Gabriela Llansol, presents us several textures and pictures that break the dividing lines of both textual and imaging spaces due to the figurative compositional process that stands within the literary universe, coloring it with words. The short stories found in this book are based on minimum action that silences the voices of the characters, expanding some other composition, a new course, not in the order of the narrative continuum, but of the textual one. The three short stories to be analyzed (“Intróito”, “A casa às avessas” e “A manhã morta”) are highlighted due to the meaningful incidence of poetic colors that set representation and the motionless universe of narrative on the move, due to the dialogue established with painting, especially with the pictures by Amadeo Modigliani (“Young Brunette”) and Picasso (“Child holding a dove”). Thus, the lines of writing and the geometric ones of painting cross with each other and draft triangles and circles, being responsible for figures that go beyond figurative language and, by doing so, making the suggested images of textuality’s “fulgor” stronger.

Os pregos na erva (1962), the first book by Maria Gabriela Llansol, presents us several textures and pictures that break the dividing lines of both textual and imaging spaces due to the figurative compositional process that stands within the literary universe, coloring it with words. The short stories found in this book are based on minimum action that silences the voices of the characters, expanding some other composition, a new course, not in the order of the narrative continuum, but of the textual one. The three short stories to be analyzed (“Intróito”, “A casa às avessas” e “A manhã morta”) are highlighted due to the meaningful incidence of poetic colors that set representation and the motionless universe of narrative on the move, due to the dialogue established with painting, especially with the pictures by Amadeo Modigliani (“Young Brunette”) and Picasso (“Child holding a dove”). Thus, the lines of writing and the geometric ones of painting cross with each other and draft triangles and circles, being responsible for figures that go beyond figurative language and, by doing so, making the suggested images of textuality’s “fulgor” stronger.
“Fulgurante” figure: the geometry of llansol’s space
Keywords: espaço textual; espaço pictórico; figuras; Llansol; Llansol; figures; textual space; imaging space